Pengaruh Pemahaman, Religiusitas dan Kualitas Pelayanan Terhadap Keputusan Nasabah Dalam Memilih Bank Syariah: Studi Kasus Masyarakat Kecamatan Sarolangun - M. Arzil Khatami; Maulana Yusuf; Nurfitri Martaliah (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Customers' decisions to save are influenced by several internal and external factors such as financial literacy and promotions. Financial literacy reflects an individual's ability to understand financial concepts, financial products, and services and to control personal financial resources independently. Promotion is one of the determining factors for the success of a marketing program. This research aims to determine the influence of sharia financial literacy and promotions both spatially and simultaneously on customers' decisions in choosing Bank Riau Kepri Syariah products. This research approach uses a quantitative descriptive approach. Data was collected using questionnaires and field observations. The research results show that partially sharia financial literacy and promotion have an influence on customers' decisions in choosing Bank Riau Kepri Syariah products. Simultaneously, the variables of sharia financial literacy and promotion influence customers' decisions in choosing Bank Riau Kepri Syariah products with a percentage of 88.2%.